A new energy indicator in damage locating vector method (DLV) for detecting multiple damaged positions in beam and truss structures - Nhan, Nguyen Minh; Du, Dinh Cong; Trung, Vo Duy; Anh, Tran Viet; Trung, Nguyen Thoi (Vietnam Journal of Mechanics, 2016)
The paper presents a new indicator called normalized energy index (nei) in damage locating vector method (DLV) for detecting multiple damaged positions in beam and truss structures. In the DLV method, a set of load vectors, which is extracted from the change in flexibility matrix between an undamaged structure and a damaged one, is applied as static loads to the undamaged structure which are evaluated via the finite element modeling. Then, the nei values are computed for each element by using the displacements. In order to verify the accuracy and efficiency of a proposed indicator, a cantilevered beam and a 14-bay planar truss are considered.